Role of Entrepreneurial Education and Self-Efficacy on Entrepreneurial Intention Among Students in Higher Education Institution - Hendy Tannady (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This look at's objective become to investigate and determine how entrepreneurship training and self-efficacy affected student subjects' entrepreneurship purpose in Jakarta. The area of this research became carried out at tertiary institutions concerning eight campuses in Jakarta. This studies became conducted for nine months, beginning in February and ending in October 2022. in this look at, we used a form of quantitative technique to assist give an explanation for how entrepreneurship schooling and self-efficacy have an effect on entrepreneurial dispositions. This look at involved students from the DKI Jakarta province. on this take a look at, the samples had been 70 students, assuming they obtained entrepreneurship education through scientific disciplines (educational) in addition to courses and seminars as well as proudly owning a business. the conclusion from the studies is that entrepreneurship schooling appreciably and favorably affects people' interest in entrepreneurship. Entrepreneurship training is meant as mastery of the competencies wished, namely recognizing new enterprise opportunities, comparing possibilities, starting groups, and developing entrepreneurial organizations. these skills are received from entrepreneurship schooling, which isn't most effective received via theory in elegance but also from publications, entrepreneurship seminars, and educational revel in.